Prospective comparative diagnostic accuracy evaluation of dynamic contrast‐enhanced (DCE) vs. dynamic susceptibility contrast (DSC) MR perfusion in differentiating tumor recurrence from radiation necrosis in treated high‐grade gliomas. Issue 2 (5th January 2019) - Zakhari, Nader; Taccone, Michael S.; Torres, Carlos H.; Chakraborty, Santanu; Sinclair, John; Woulfe, John; Jansen, Gerard H.; Cron, Greg O.; Thornhill, Rebecca E.; McInnes, Matthew D.F.; Nguyen, Thanh B.
Abstract : Background: The appearance of a new enhancing lesion after surgery and chemoradiation for high‐grade glioma (HGG) presents a common diagnostic dilemma. Histopathological analysis remains the reference standard in this situation. Purpose: To prospectively compare the diagnostic accuracy of dynamic contrast‐enhanced (DCE) vs. dynamic susceptibility contrast (DSC) in differentiating tumor recurrence (TR) from radiation necrosis (RN). Study Type: Prospective diagnostic accuracy study. Population: In all, 98 consecutive treated HGG patients with new enhancing lesion. We excluded 32 patients due to inadequate follow‐up or technical limitation. Field Strength/Sequence: 3 T DCE and DSC MR. Assessment: Histogram and hot‐spot analysis of cerebral blood volume (CBV), corrected CBV, K trans, area under the curve (AUC), and plasma volume (Vp). The reference standard of TR and/or RN was determined by histopathology in 43 surgically resected lesions or by clinical/imaging follow‐up in the rest. Statistical Tests: Mann–Whitney U ‐tests, receiver operating characteristic (ROC) curve, and logistic regression analysis. Results: A total of 68 lesions were included. There were 37 TR, 28 RN, and three lesions with equal proportions of TR and RN. TR had significantly higher CBV, corrected CBV, CBV ratio, corrected CBV ratio, AUC ratio, and Vp ratio ( P < 0.05) than RN on hot‐spot analysis. CBV had the highest diagnostic accuracy (AUROC 0.71). On histogram analysis, TR had higher CBV and corrected CBV maximal value compared with RN ( P = 0.006, AUROC = 0.70). Only CBV on hot‐spot analysis remained significant after correction for multiple comparison, with no significant improvement in diagnostic accuracy when using a combination of parameters (AUROC 0.71 vs. 0.76, P = 0.24). Data Conclusion: DSC‐derived CBV is the most accurate perfusion parameter in differentiating TR and RN. DSC and DCE‐derived parameters reflecting the blood volume in an enhancing lesion are more accurate than the DCE‐derived parameter K trans . Clinical practice may be best guided by blood volume measurements, rather than permeability assessment for differentiation of TR from RN. Level of Evidence : 1 Technical Efficacy Stage : 4 J. Magn. Reson. Imaging 2019;50:573–582.